Fresh Evidence for Platelets as Neuronal and Innate Immune Cells: Their Role in the Activation, Differentiation, and Deactivation of Th1, Th17, and Tregs during Tissue Inflammation - Ponomarev, Eugene D. (Frontiers in Immunology, 2018)
Recent studies suggest that in addition to their common function in the regulation of thrombosis and hemostasis, platelets also contribute to tissue inflammation affecting adaptive immunity. Platelets have a number of pro-inflammatory and regulatory mediators stored in their alpha- and dense granules, which are promptly released at sites of inflammation or tissue injury. Platelet-derived mediators include cytokines (IL-1α, IL-1β, TGFβ1), chemokines (CXCL4, CCL3), immunomodulatory neurotransmitters (serotonin, dopamine, epinephrine, histamine, GABA) and other low molecular weight mediators. In addition, activated platelets synthesize a number of lipid pro-inflammatory mediators such as platelets-activating factor, and prostaglandins/thromboxanes. Notably, platelets express multiple TLRs and MHC class I on their surface and store IgG in their α-granules. Platelet-derived factors are highly effective at directly or indirectly modulating the priming and effector function of various subsets of T cells. Besides secreting soluble factors, activated platelets upregulate a number of integrins, adhesion molecules and lectins, leading to the formation of platelet-T cells aggregates. Activated platelets are able to instantly release neurotransmitters acting similar to neuronal pre-synaptic terminals, affecting CD4 T cells and other cells in close contact with them. The formation of platelet-T cell aggregates modulates the functions of T cells via direct cell-cell contact interactions and the local release of soluble factors including neurotransmitters. New data suggest an important role for platelets as neuronal and innate-like cells that directly recognize damage- or pathogen- associated molecular patterns, and instantly communicate with T cells.